2015
DOI: 10.1016/j.schres.2015.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of oligodendrocyte precursors is impaired in the prefrontal cortex in schizophrenia

Abstract: The pathophysiology of schizophrenia involves disturbances of information processing across brain regions, possibly reflecting, at least in part, a disruption in the underlying axonal connectivity. This disruption is thought to be a consequence of the pathology of myelin ensheathment, the integrity of which is tightly regulated by oligodendrocytes. In order to gain insight into the possible neurobiological mechanisms of myelin deficit, we determined the messenger RNA (mRNA) expression profile of laser captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 75 publications
4
59
0
2
Order By: Relevance
“…In turn, excess of astrocytic human-specific expression differences matches histological differences reported between humans and the other primate species for interlaminar astrocytes, polarized astrocytes, and varicose projection astrocytes [Oberheim et al, 2009;Falcone et al, 2018]. Similarly, oligodendrocyte progenitor cells showing rapid expression evolution in human caudate nucleus were reported to dysfunction in the caudate nucleus of schizophrenia patients [Georgieva et al, 2006;Uranova et al, 2007;Cassoli et al, 2015;Mauney et al, 2015], a disorder suggested to affect aspects of cognition particular to humans [Konopka and Geschwind, 2010;Dean, 2009].…”
Section: Discussionsupporting
confidence: 58%
“…In turn, excess of astrocytic human-specific expression differences matches histological differences reported between humans and the other primate species for interlaminar astrocytes, polarized astrocytes, and varicose projection astrocytes [Oberheim et al, 2009;Falcone et al, 2018]. Similarly, oligodendrocyte progenitor cells showing rapid expression evolution in human caudate nucleus were reported to dysfunction in the caudate nucleus of schizophrenia patients [Georgieva et al, 2006;Uranova et al, 2007;Cassoli et al, 2015;Mauney et al, 2015], a disorder suggested to affect aspects of cognition particular to humans [Konopka and Geschwind, 2010;Dean, 2009].…”
Section: Discussionsupporting
confidence: 58%
“…One presumption is that they are consequences of oligodendroglial deficits because variations in the genes that encode oligodendrocyte and myelin proteins, such as OLIG2, MBP, PLP1, MOG, MOBP, CNP, and MAG, have been associated with schizophrenia (reviewed in (Roussos and Haroutunian ), and lower levels of expression of these proteins were observed in schizophrenia brains post‐mortem (Hakak et al, ; Mauney et al, ; Tkachev et al, ). Moreover, a recent study reported a decrease in the density of OLIG2+ cells and an increase in PDGFRA expression in the prefrontal cortex (Mauney et al, ). Highly reminiscent of these findings in schizophrenia, the levels of all the investigated myelin proteins in this study were reduced in the cortex in adult St8sia2 −/− mice, and St8sia2 −/− OPCs exhibited an increase in the level of PDFGRα in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is essential for oligodendrocyte and motor neuron development in the spinal cord [Ono et al, 2008], and for oligodendrocyte function, the impairment of which is thought to be a primary pathogenic event in SZ, specifically affecting the prefrontal cortex [Georgieva et al, 2006;Mauney et al, 2015]. Indeed, in our network, OLIG2 is also linked to GFAP , which encodes a hallmark structural component of mature astrocytes.…”
Section: Functional Implication and Biological Interpretation Of Domementioning
confidence: 93%